ChemInform Abstract: Gold versus Silver Catalyzed Intramolecular Hydroarylation Reactions of [(3‐Arylprop‐2‐ynyl)oxy]benzene Derivatives. Issue 20 (25th April 2013) - Arcadi, Antonio; Blesi, Federico; Cacchi, Sandro; Fabrizi, Giancarlo; Goggiamani, Antonella; Marinelli, Fabio
Abstract This reaction proceeds via a 6‐endo cyclization.